2020
DOI: 10.1371/journal.pone.0231260
|View full text |Cite
|
Sign up to set email alerts
|

The identification and treatment of mental health and substance misuse problems in sexual assault services: A systematic review

Abstract: BackgroundSpecialist sexual assault services, which collect forensic evidence and offer holistic healthcare to people following sexual assault, have been established internationally. In England, these services are called sexual assault referral centres (SARCs). Mental health and substance misuse problems are common among SARC attendees, but little is known about how SARCs should address these needs. This review aims to seek and synthesise evidence regarding approaches to identification and support for mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 98 publications
1
19
0
Order By: Relevance
“…However, few services seem to tailor interventions to survivors and many of the included studies suggested that referring clients on for needed follow-up was difficult (Brooker & Durmaz, 2015 ; Holly & Horvath, 2012 ; Zweig et al, 2002 ). This finding is in line with other recent reviews of the literature, which identified wide variations in the provision of mental health and substance abuse services at SA centres (Stefanidou et al, 2020 ), and found that pathways from SA services to mental health services are often difficult (Brooker, Hughes, Lloyd-Evans, & Stefanidou, 2019 ). In addition, psychotherapy alone may be insufficient to adequately support survivors with multiple needs as highlighted by Akinsulure-Smith ( 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, few services seem to tailor interventions to survivors and many of the included studies suggested that referring clients on for needed follow-up was difficult (Brooker & Durmaz, 2015 ; Holly & Horvath, 2012 ; Zweig et al, 2002 ). This finding is in line with other recent reviews of the literature, which identified wide variations in the provision of mental health and substance abuse services at SA centres (Stefanidou et al, 2020 ), and found that pathways from SA services to mental health services are often difficult (Brooker, Hughes, Lloyd-Evans, & Stefanidou, 2019 ). In addition, psychotherapy alone may be insufficient to adequately support survivors with multiple needs as highlighted by Akinsulure-Smith ( 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…These findings highlight a critical need to increase mental health services for survivors of sexual violence, particularly telehealth options, that are accessible both during and following crises. Researchers have advocated for increasing the availability of mental health services delivered through sexual assault service providers (SASPs), possibly through partnerships with local counseling providers ( Stefanidou et al, 2020 ). Specifically, rural SASPs have successfully partnered with university-based mental health programs to provide care, and specifically telehealth counseling, to rural victims of sexual violence who otherwise lacked access ( Gray et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was because the policies/service specifications used to inform the extraction form (i.e Health and Justice, 2018; NHS England, 2016) contained few recommendations or indicators, which related to mental health or substance use, highlighting a lack of guidance around these issues at the macro-level. To address this, two new core principles and associated indicators were developed by examining and drawing on the results of our systematic review (Stefanidou et al, 2020) around effective mental health and substance use pathways within SARCs. The additional key principles were: (1) ‘ Identification of mental health and substance use needs ’ and (2) ‘ How the service addresses mental health and substance use needs’ .…”
Section: Methodsmentioning
confidence: 99%
“…For example, the SARC process can take several hours, meaning a person prescribed opiate substitution therapy may miss a dose or more and start to experience significant discomfort (Clinical, 2017; Independent Expert Working Group, 2017). When considering how examinations are scheduled for intoxicated or withdrawing service users, a relevant theory from the realist review was identified: ‘ If SARCs don't stock medication for substance use, then service users with withdrawal symptoms can't be managed within the SARC and may have to go to A&E/rearrange Forensic Medical Examination’ (Stefanidou et al, 2020). In order to test this theory, a number of questions were generated to be asked during staff interviews, for example, ‘ do you stock medication for substance use in the SARC?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation